1995
DOI: 10.1128/iai.63.10.4138-4142.1995
|View full text |Cite
|
Sign up to set email alerts
|

Chronic respiratory mycoplasmosis in C3H/HeN and C57BL/6N mice: lesion severity and antibody response

Abstract: Mycoplasma pneumoniae is a leading, worldwide cause of death and disability due to pneumonia. Mycoplasma pulmonis infection in mice is an invaluable model for the study of host defenses against respiratory mycoplasmas in vivo. C3H/HeN mice are much more susceptible to acute inflammatory lung disease due to M. pulmonis than C57BL/6N mice, but little is known about the chronic disease in these mouse strains. We infected C3H/HeN and C57BL/6N mice with 10 4 CFU of M. pulmonis UAB CT and evaluated them at weekly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 24 publications
(34 reference statements)
3
29
0
1
Order By: Relevance
“…Previous studies have shown that M. pulmonis infection in the airways of F344 rats causes chronic inflammation with angiogenesis, characterized by extensive proliferation of mucosal blood vessels (14,16). Recently, we characterized the vascular remodeling in the airways of C3H/HeNCr mice, a strain known to be sensitive to M. pulmonis (36). Airway blood vessels of F344 rats and C3H/HeNCr mice infected with M. pulmonis are similar in that both have normal baseline permeability (with no intervention apart from the infection) but both have exaggerated leakiness after exposure to substance P (14, 16).…”
Section: Murine Models Of Angiogenesismentioning
confidence: 99%
“…Previous studies have shown that M. pulmonis infection in the airways of F344 rats causes chronic inflammation with angiogenesis, characterized by extensive proliferation of mucosal blood vessels (14,16). Recently, we characterized the vascular remodeling in the airways of C3H/HeNCr mice, a strain known to be sensitive to M. pulmonis (36). Airway blood vessels of F344 rats and C3H/HeNCr mice infected with M. pulmonis are similar in that both have normal baseline permeability (with no intervention apart from the infection) but both have exaggerated leakiness after exposure to substance P (14, 16).…”
Section: Murine Models Of Angiogenesismentioning
confidence: 99%
“…Consistent with this hypothesis, experimental infections of mice with M. pulmonis and MHV have been reported to cause early after challenge (1 and 4 days, respectively) a marked immunodepression lasting at least 28 days [21,22]. Since the earliest that antibodies to MHV and to M. pulmonis can be detected after a challenge is 10 days for the former pathogen [19] and 14 days for the latter [23], it is very likely that the SPF animals used in our experiments got infected with MHV (and in some instances with M. pulmonis) during the very first days after their arrival in our vivarium. If so, these animals were in all likelihood within the period of immunomodulation by the time they were inoculated with the melanoma cells.…”
Section: Discussionmentioning
confidence: 69%
“…Pathogen-free male C3H mice (C3H/HeNCrlBR, Charles River Laboratories, Hollister, CA) 7-9 weeks of age (17-21 g) were anesthetized with ketamine (87 mg/kg, Parke-Davis, Morris Plains, NJ) and xylazine (13 mg/kg, Ben Venue Laboratories, Bedford, OH) i.p. and given 10 5 CFU M. pulmonis UAB CT strain 12,13 by nasal inoculation (25 l per nostril). Pathogen-free and M. pulmonis-infected mice were housed separately under barrier conditions.…”
Section: Chronic Airway Inflammationmentioning
confidence: 99%
“…Mycoplasma pulmonis, which attaches to the airway epithelium, induces chronic airway inflammation in mice. 12,13 Associated with this inflammation is a large influx of leukocytes into the airway lumen. 4 M. pulmonis infection also induces enlargement and proliferation of the airway microvasculature and changes in EC phenotype.…”
mentioning
confidence: 99%